Implementasi Sistem Informasi Manajemen Masjid Berbasis Web - Herfandi Herfandi; Fahri Hamdani (INFORMAL: Informatics Journal, 2022)
The mosque is a place of worship for Muslims. The mosque plays an important role as the center of Muslim activities. However, behind the mosque's very important role in social activities, it is not balanced with the needs of today's modern society. Therefore, this study implements a management information system (MIS) in mosques. This study resulted in a mosque SIM which was developed on a web-based basis so that it was easily accessible and the software development method used the waterfall so that the SIM that was built was quickly resolved and the development process to implementation and hosting. The features for mosque SIM visitors: information on the call to prayer/prayer schedule, parameter information (qibla direction), financial data information (incoming and outgoing), information on mosque donations/alms, and contact information for contacting the mosque SIM manager. Admin features: manage mosque staff data (create, edit and delete), input data types for donation/alms categories, backup and restore SIM, print officer data, and view the history of what activities have been done by the admin. Officer features: managing activity agendas, managing mosque funds (transfer confirmation, mosque cash profit, income data, expenditure data), and managing report management that will be used as a reference for making decisions/policies. The mosque SIM is expected to help and facilitate mosque officials and administrators in managing mosque activities and finances.